The Neuro-endocrinological Role of Microbial Glutamate and GABA Signaling - Mazzoli, Roberto; Pessione, Enrica (Frontiers in Microbiology, 2016)
Gut microbiota provides the host with multiple functions (e.g., by contributing to food digestion, vitamin supplementation and defense against pathogenic strains) and interacts with the host organism through both direct contact (e.g., through surface antigens) and soluble molecules, which are produced by the microbial metabolism. The existence of the so-called gut-brain axis of bi-directional communication between the gastrointestinal tract and the central nervous system also supports a communication pathway between the gut microbiota and neural circuits of the host, including the central nervous system. An increasing body of evidence has shown that gut microbiota is able to modulate gut and brain functions, including the mood, cognitive functions and behavior of humans. Nonetheless, given the extreme complexity of this communication network, its comprehension is still at its early stage. The present contribution will attempt to provide a state-of-the art description of the mechanisms by which gut microbiota can affect the gut-brain axis and the multiple cellular and molecular communication circuits (i.e., neural, immune and humoral). In this context, special attention will be paid to the microbial strains that produce bioactive compounds and display ascertained or potential probiotic activity. Several neuroactive molecules (e.g., catecholamines, histamine, serotonin and trace amines,) will be considered, with special focus on Glu and GABA circuits, receptors and signaling. From the basic science viewpoint, “microbial endocrinology” deals with those theories in which neurochemicals, produced by both multicellular organisms and prokaryotes (e.g., serotonin, GABA, glutamate), are considered as a common shared language that enables interkingdom communication. With regards to its application, research in this area opens the way toward the possibility of the future use of neuroactive molecule-producing probiotics as therapeutic agents for the treatment of neurogastroenteric and/or psychiatric disorders.